Silicon-carbon negative electrode material based on electrostatic spinning as well as preparation method and application of silicon-carbon negative electrode material

Through electrospinning technology combined with sub-silicon oxide, silicon carbon anode material with good flexibility and self-supporting structure was prepared, which solved the problem of large volume changes in the negative electrode material of lithium-ion battery during storage and achieved efficient electrochemical performance improvement.

CN120191938APending Publication Date: 2025-06-24SOUTH CHINA NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510349525.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-06-24

AI Technical Summary

Technical Problem

The volume of existing lithium-ion battery anode materials changes greatly during storage, resulting in unstable electrochemical performance and difficult to meet the high market requirements for endurance and safety performance.

Method used

Using electrospinning technology combined with sub-silicon oxide, silicon carbon anode material with good flexibility and self-supporting structure is prepared by generating sub-silicon particles in situ in carbon nanofiber materials and coated through core-shell structures.

Benefits of technology

It realizes efficient coating and structural stability of silicon negative electrode materials, and improves the electrochemical performance of lithium-ion batteries, including high specific capacity, excellent rate performance and long-term cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120191938A_ABST
    Figure CN120191938A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a silicon-carbon self-supporting flexible negative electrode material based on electrostatic spinning and application of the silicon-carbon self-supporting flexible negative electrode material in a lithium ion battery. According to the preparation method, the silicon monoxide particles can be generated in situ in the carbon nanofiber material, the coating effect is good, the flexibility is relatively good, and the carbon nanofiber material can be directly used as a lithium ion battery negative electrode material to improve the electrochemical performance of a lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of anode materials for lithium-ion batteries, and particularly relates to a preparation method of a silicon-carbon self-supporting flexible anode material based on electrospinning and its application in lithium-ion batteries. Background Art

[0002] Due to its advantages such as high energy density, good cycle stability, environmental friendliness, and wide operating temperature range, lithium-ion batteries have successfully replaced traditional batteries with serious pollution (such as lead-acid batteries, nickel-metal hydride batteries, nickel-cadmium batteries) in the market. As one of the most critical links in the lithium-ion battery industry, the production cost of the anode material of lithium-ion batteries can account for 25-28% of the total battery cost. With the market, especially the power battery market, putting forward higher and higher requirements for the endurance and safety performance of lithium-ion batteries, the performance requirements for the anode material are also getting higher and higher. The theoretical specific capacity of silicon material is 4200 mAh / g, which is more than 10 times that of traditional graphite anode materials. Therefore, it has attracted much attention and is considered very likely to replace traditional graphite electrodes and become the anode material for the next generation of high-energy-density lithium-ion batteries.

[0003] At present, common preparation methods for silicon-carbon anodes include chemical vapor deposition, spray drying, ball milling, hydrothermal method, sol-gel method, electrospinning method, etc. The application of electrospinning in lithium-ion batteries has received particular attention. Electrospun porous carbon nanofibers can form a film directly, have a self-supporting structure, can be directly used as an electrode without a conductive agent and a binder, which can simplify the electrode preparation process and reduce costs. In addition, an appropriate combination of polymers and carbonization temperature provides the fibers with a porous structure and conductivity, thereby improving the charge storage capacity. Therefore, based on the high aspect ratio, large specific surface area, good conductivity and flexibility, electrospun CNFs composites are also used as anode materials for lithium-ion batteries and have excellent electrochemical performance. These carbonized composite porous carbon nanofibers can achieve fast ion insertion / extraction by reducing the ion diffusion length. More importantly, silicon particles can be directly added to the polyacrylonitrile (PAN) precursor to produce a composite fiber membrane. The combination of electrospinning and silicon materials aims to generate an electrode with excellent electrochemical stability and structural integrity by constructing a hierarchical structure and providing a good carrier transport network, thereby solving the volume change problem of silicon during lithium-ion storage. Summary of the Invention

[0004] The purpose of the present invention is to provide a method for preparing a silicon anode material by combining silicon monoxide with a core-shell structure and electrospinning technology in view of the deficiencies of the prior art. This method can enable the in-situ generation of sub-silicon particles in the carbon nanofiber material, and has a good coating effect, good flexibility, and can be directly used as an anode material for lithium-ion batteries to improve the electrochemical performance of lithium-ion batteries.

[0005] To solve the above problems, the present invention adopts the following technical solutions:

[0006] According to one aspect of the present invention, an object of the present invention is to provide a preparation method of an electrospun silicon-carbon anode material, comprising the following steps:

[0007] S1. Dissolve zinc nitrate hexahydrate in deionized water, and name it solution A; dissolve 2-methylimidazole and cetyltrimethylammonium bromide in deionized water, and name it solution B.

[0008] S2. After stirring solutions A and B evenly at room temperature, add solution A to solution B, continue stirring for a period of time, then let it stand. Centrifuge the precipitate, wash it three times with water and anhydrous ethanol respectively, and dry it at 70 °C for 12 h to obtain ZIF-8 material.

[0009] S3. Disperse the ZIF-8 material prepared in step S2 in a mixed solution of anhydrous ethanol and water, add 2-methylimidazole (2-MI) and cetyltrimethylammonium bromide (CTAB), ultrasonically disperse this solution evenly, and dropwise add two types of organosilicon sources tetraethyl orthosilicate (TEOS) and 3-aminopropyltrimethoxysilane (APTMS) drop by drop under stirring. The two organosilicon sources are added alternately every half hour, and the operation is carried out 4 times. Then stir the above solution, centrifuge it, wash it with deionized water, and dry it.

[0010] S4. Ultrasonically disperse the material obtained in step S3 in DMF, add polyacrylonitrile and mix evenly to obtain a precursor solution, and prepare a fiber membrane using an electrospinning machine.

[0011] S5. Pre-oxidize the fiber membrane in a muffle furnace at a certain temperature for a period of time, and then heat-treat it under argon protection to obtain a silicon anode material.

[0012] Preferably, in step S1, 0.58 g of zinc nitrate hexahydrate is added and dissolved in 20 ml of deionized water, and 9.08 g of 2-methylimidazole and 0.008 g of cetyltrimethylammonium bromide are respectively dissolved in 140 ml of deionized water.

[0013] Preferably, the stirring time in step S2 is within 5 - 10 min, and the standing time is 12 h to 36 h.

[0014] Preferably, in step S3, take 0.3 g of the material ZIF-8 prepared in step S2 and dissolve it in a mixed solution of 120 mL of ethanol and 198 mL of water, add 1.5 g of CTAB and 1.5 g of 2-MI; the ultrasonic time is 0.5 h, then stir for 10 min, and the amount of each dropwise addition of the two types of organosilicon sources tetraethyl orthosilicate (TEOS) and 3-aminopropyltrimethoxysilane (APTMS) is 0.5 ml.

[0015] Preferably, in step S3, the dosage ratio of the two types of silicone sources, tetraethyl orthosilicate (TEOS) and 3-aminopropyltrimethoxysilane (APTMS), is 1:1 (volume ratio) to 1:1.5 (volume ratio).

[0016] Preferably, in step S4, based on 5 ml of DMF, the dosage of the material obtained in step S3 is 0.1 g to 0.4 g.

[0017] Preferably, in step S4, based on 5 ml of DMF, the dosage of polyacrylonitrile is 0.6 g.

[0018] Preferably, in step S4, the electrospinning speed is 0.08 mm / min to 0.12 mm / min, the voltage is 10 KV to 18 KV, and the receiving distance is 12 mm to 15 mm.

[0019] Preferably, in step S5, the pre-oxidation temperature is 200 - 250 °C, the stabilization time is 2 h, and the heating rate is 2 °C·min -1 , the calcination temperature in argon is 700 °C, the heat treatment time is 3 h, and the heating rate is 5 °C·min -1 .

[0020] According to another aspect of the present invention, another object of the present invention is to provide an electrospun silicon-carbon anode material prepared by the above preparation method.

[0021] According to another aspect of the present invention, another object of the present invention is to provide the use of the electrospun silicon-carbon anode material as an anode material for a lithium-ion battery.

[0022] According to another aspect of the present invention, another object of the present invention is to provide a lithium-ion battery, which uses the electrospun silicon-carbon anode material as the anode material.

[0023] Advantageous Effects

[0024] Compared with the prior art, the advantageous effects of the present invention are as follows: The nanofibers obtained by electrospinning can be directly formed into a film, having a self-supporting structure and good flexibility, and can be directly pressed into a sheet for use as an electrode without a conductive agent and a binder, which can simplify the electrode preparation process and reduce costs. At the same time, the appropriate combination of the polymer and the carbonization temperature provides the fiber with a porous structure and conductivity, thereby improving the charge storage capacity. The prepared silicon-based material as the anode of a button battery, through corresponding physical and electrochemical characterization means, has confirmed that this anode material has high ionic and electronic conductivity, high specific capacity, excellent rate performance, and long-term cycle life. Description of the Drawings

[0025] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following will briefly introduce the drawings required for the description of the specific embodiments or the prior art. Obviously, the drawings in the following description are some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings.

[0026] Figure 1 SEM images of ZIF-8(a) and ZIF-8@SiOx(b) prepared in Example 2 under a scanning electron microscope;

[0027] Figure 2 SEM images of Zn-NC@SiOx / CNFs prepared in Examples 1 to 4 under a scanning electron microscope;

[0028] Figure 3 XRD and FTIR images of ZIF-8, ZIF-8@SiOx and the final product ZIF-8@SiOx materials prepared in Example 2.

[0029] Figure 4 High-resolution XPS spectra of C1s, O1s, N1s, and Si 2p of Zn-NC@SiOx / CNFs prepared in Example 2;

[0030] Figure 5 Raman spectra of Zn-NC@SiOx / CNFs materials with different contents of ZIF-8@SiOx prepared in Examples 1 to 4;

[0031] Figure 6 For the half-cells assembled with electrodes of Zn-NC@SiOx / CNFs materials with different contents of ZIF-8@SiOx prepared in Examples 1 to 4 and Comparative Example 1 at a current density of 0.1 A·g -1 Cyclic test curves and rate performance graphs;

[0032] Figure 7 Cyclic specific capacity test curves of Zn-NC@SiOx / CNFs with different contents of ZIF-8@SiOx prepared in Examples 1 to 4 and Comparative Example 1.

[0033] Figure 8 Appearance of Zn-NC@SiOx / CNFs prepared in Example 2 and digital photos after bending and folding. Specific Embodiments

[0034] In the following, preferred embodiments of the present disclosure will be described in detail with reference to the accompanying drawings. Before the description, it should be understood that the terms used in the specification and the appended claims should not be construed as limited to the general and dictionary meanings, but should be interpreted based on the principle of appropriately defining terms to allow the inventor to make the best interpretation, based on the meanings and concepts corresponding to the technical level of the present invention. Therefore, the description herein is only a preferred example for illustrative purposes and is not intended to limit the scope of the present invention. Thus, it should be understood that other equivalent implementations and modifications can be made without departing from the spirit and scope of the present invention.

[0035] In this document, the terms "comprising", "including", "having", "containing" or any other similar terms are all open conjunctions, which are intended to cover non-exclusive inclusions. For example, a composition or article containing plural elements is not limited only to the elements listed herein, but may also include other elements that are not explicitly listed but are normally inherent in the composition or article. In addition, unless there is a clear contrary indication, the term "or" refers to an inclusive "or" rather than an exclusive "or". For example, any of the following situations satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), A and B are both true (or exist). Furthermore, in this document, the interpretations of the terms "comprising", "including", "having", "containing" should be regarded as having specifically disclosed and simultaneously covered closed or semi-closed conjunctions such as "consisting of" and "substantially consisting of".

[0036] In this document, all features or conditions defined in the form of numerical ranges or percentage ranges are only for the sake of brevity and convenience. Accordingly, the description of a numerical range or percentage range should be regarded as having covered and specifically disclosed all possible sub-ranges and individual values within the range, especially integer values. For example, the description of the range "1 to 8" should be regarded as having specifically disclosed all sub-ranges such as 1 to 7, 2 to 8, 2 to 6, 3 to 6, 4 to 8, 3 to 8, etc., especially the sub-ranges defined by all integer values, and should be regarded as having specifically disclosed the individual values such as 1, 2, 3, 4, 5, 6, 7, 8 within the range. Unless otherwise specified, the foregoing interpretation method applies to all contents of the present invention, regardless of the breadth of the range.

[0037] If a quantity or other numerical or parameter is expressed in the form of a range, a preferred range or a series of upper and lower limits, it should be understood that all ranges constituted by any pair of the upper limit or preferred value of the range and the lower limit or preferred value of the range have been specifically disclosed herein, regardless of whether these ranges are separately disclosed. In addition, when a numerical range is mentioned in this document, unless otherwise stated, the range should include its endpoints and all integers and fractions within the range.

[0038] In this article, on the premise of achieving the invention purpose, the numerical value should be understood as having the precision of the significant digits of that numerical value. For example, the number 40.0 should be understood as covering the range from 39.50 to 40.49.

[0039] The following examples are only listed as examples of the implementation schemes of the present invention and do not constitute any limitation to the present invention. Those skilled in the art can understand that modifications within the scope not deviating from the essence and concept of the present invention fall within the protection scope of the present invention. Unless otherwise specified, the reagents and instruments used in the following examples are all commercially available products.

[0040] Example 1:

[0041] Synthesis of ZIF-8 nanoblocks: Dissolve 0.58 g of Zn(NO3)2·6H2O in 20 mL of deionized water and name it solution A; dissolve 9.08 g of 2-MI and 0.008 g of CTAB in 140 mL of deionized water and name it solution B. After stirring solutions A and B for 10 min, add solution A to solution B, continue stirring for 5 min, then let it stand for 12 h. Centrifuge the precipitate at 10000 rpm for 7 min, wash it several times with water and ethanol respectively, and dry the product at 70 °C for 12 h.

[0042] Synthesis of ZIF-8@SiOx: Dissolve 0.3 g of the above-prepared ZIF-8 nanoblocks in a mixed solution of 120 mL of ethanol and 198 mL of water, add 1.5 g of CTAB and 1.5 g of 2-MI, ultrasonically disperse this solution for 0.5 h, then stir for 10 min, and then dropwise add 0.5 mL of TEOS. Next, add 0.5 mL of APTMS and 0.5 mL of TEOS every half hour, 0.5 mL of APTMS, and then stir the above solution for 2 h, centrifuge and wash it three times with deionized water and ethanol, and dry it at 70 °C for 12 h to obtain a core-shell structured ZIF-8@SiOx material.

[0043] Take 0.1 g of the obtained ZIF-8@SiOx and ultrasonically disperse it in 5 ml of DMF, and mix it with 0.6 g of PAN overnight under stirring to obtain a precursor solution for electrospinning. Then, form ZIF-8@SiOx@PAN nanofibers on a release paper through electrospinning of the precursor solution. The electrospinning needle used is a 23G stainless steel needle, and the electrospinning parameters are positive voltage: 9.19 KV, negative voltage: -2.49 KV, pushing speed: 0.05 mm / min, stroke set at 200 mm, translation speed: 350 mm / min, and a flat receiver is used. Stabilize the obtained ZIF-8@SiOx@PAN nanofiber membrane in air at 250 °C for 2 h with a slope of 2 °C·min -1 Then immediately at a rate of 5 °C·min in argon -1The heating rate is heat-treated at 700 °C for 3 h to obtain Zn-NC@SiOx 0.1 / CNFs electrospun silicon-carbon anode material.

[0044] Finally, the calcined fiber membrane is cooled to room temperature and pressed into a disc with a diameter of 12 mm, which is directly used as an electrode.

[0045] Assemble and test the battery according to the following method:

[0046] The electrolyte is composed of 1 M LiPF6 in an aqueous solution with a mass ratio of diethyl carbonate (DEC), dimethyl carbonate (DMC), and ethylene carbonate (EC) of 1:1:1. Metallic lithium is used as the positive electrode, and the electrospun silicon-carbon anode material prepared in this example is used as the negative electrode material. Assemble a button battery (CR2032) in a glove box under an Ar atmosphere for electrical performance testing. The assembled button battery is subjected to charge-discharge and cycling tests on a Neware test system.

[0047] Example 2:

[0048] Synthesis of ZIF-8 nanoblocks: Dissolve 0.58 g of Zn(NO3)2·6H2O in 20 mL of deionized water, and name it solution A; dissolve 9.08 g of 2-MI and 0.008 g of CTAB in 140 mL of deionized water, and name it solution B. After stirring solutions A and B for 10 min, add solution A to solution B, continue stirring for 5 min, then let it stand for 12 h. Centrifuge the precipitate at 10000 rpm for 7 min, and wash it three times with water and ethanol respectively. The product is dried at 70 °C for 12 h.

[0049] Synthesis of ZIF-8@SiOx: Dissolve 0.3 g of the above-prepared ZIF-8 nanoblocks in a mixed solution of 120 mL of ethanol and 198 mL of water, add 1.5 g of CTAB and 1.5 g of 2-MI, ultrasonically disperse this solution for 0.5 h, then stir for 10 min, and then dropwise add 0.5 mL of TEOS. Next, add 0.5 mL of APTMS, 0.5 mL of TEOS, and 0.5 mL of APTMS every half hour in turn. Then stir the above solution for 2 h, centrifuge and wash it three times with deionized water and ethanol, and dry it at 70 °C for 12 h to obtain the core-shell structured ZIF-8@SiOx material.

[0050] Take 0.2 g of the obtained ZIF-8@SiOx and ultrasonically disperse it in 5 ml of DMF. Then mix it with 0.6 g of PAN overnight under stirring to obtain a precursor solution for electrospinning. Subsequently, the precursor solution is electrospun to form ZIF-8@SiOx@PAN nanofibers on a release paper. Among them, a 23G stainless steel needle is used as the electrospinning needle, and the electrospinning parameters are: positive voltage: 9.19 KV, negative voltage: -2.49 KV, pushing speed: 0.05 mm / min, stroke set at 200 mm, translation speed: 350 mm / min, and a flat receiver is used. The obtained ZIF-8@SiOx@PAN nanofiber membrane is stabilized in air at 250 °C for 2 h with a slope of 2 °C·min -1 . Then immediately heat-treat it in argon at a heating rate of 5 °C·min -1 at 700 °C for 3 h to obtain Zn-NC@SiOx 0.2 / CNFs electrospun silicon-carbon anode material.

[0051] Finally, cool the calcined fiber membrane to room temperature and press it into a disc with a diameter of 12 mm, which is directly used as an electrode. Assemble and test the charge-discharge and cycle performance of the battery according to the same method as in Example 1.

[0052] Example 3:

[0053] Synthesis of ZIF-8 nanoblocks: Dissolve 0.58 g of Zn(NO3)2·6H2O in 20 mL of deionized water, and name it Solution A; dissolve 9.08 g of 2-MI and 0.008 g of CTAB in 140 mL of deionized water, and name it Solution B. After stirring Solutions A and B for 10 min, add Solution A to Solution B, continue stirring for 5 min, then let it stand for 12 h. Centrifuge the precipitate at 10000 rpm for 7 min, and wash it several times with water and ethanol respectively. The product is dried at 70 °C for 12 h.

[0054] Synthesis of ZIF-8@SiOx: Dissolve 0.3 g of the above-prepared ZIF-8 in a mixed solution of 120 mL of ethanol and 198 mL of water, add 1.5 g of CTAB and 1.5 g of 2-MI, ultrasonically disperse this solution for 0.5 h, then stir for 10 min, and then dropwise add 0.5 mL of TEOS. Next, add 0.5 mL of APTMS, 0.5 mL of TEOS, and 0.5 mL of APTMS every half hour in turn. Then stir the above solution for 2 h, centrifuge it, and wash it three times with deionized water and ethanol, and dry it at 70 °C for 12 h to obtain a core-shell structured ZIF-8@SiOx material.

[0055] Take 0.3 g of the obtained ZIF-8@SiOx and disperse it ultrasonically in 5 ml of DMF. Mix it with 0.6 g of PAN overnight under stirring to obtain a precursor solution for electrospinning. Then, the precursor solution is electrospun to form ZIF-8@SiOx@PAN nanofibers on a release paper. Among them, a 23G stainless steel needle is used as the spinning needle, and the electrospinning parameters are positive voltage: 9.19 KV, negative voltage: -2.49 KV, pushing speed: 0.05 mm / min, stroke set at 200 mm, translation speed: 350 mm / min, and a flat receiver is used. The obtained ZIF-8@SiOx@PAN nanofiber membrane is stabilized in air at 250 °C for 2 h with a slope of 2 °C·min -1 . Then immediately heat-treat it in argon at a heating rate of 5 °C·min -1 for 3 h at 700 °C to obtain Zn-NC@SiOx 0.3 / CNFs electrospun silicon-carbon anode material.

[0056] Finally, cool the calcined fiber membrane to room temperature, press it into a disc with a diameter of 12 mm, and directly use it as an electrode. Assemble a test battery in the same method as in Example 1 for charge-discharge and cycling tests.

[0057] Example 4:

[0058] Synthesis of ZIF-8 nanoblocks: Dissolve 0.58 g of Zn(NO3)2·6H2O in 20 mL of deionized water and name it Solution A; dissolve 9.08 g of 2-MI and 0.008 g of CTAB in 140 mL of deionized water and name it Solution B. After stirring Solutions A and B for 10 min, add Solution A to Solution B, continue stirring for 5 min, then let it stand for 12 h. Centrifuge the precipitate at 10000 rpm for 7 min, wash it several times with water and ethanol respectively, and dry the product at 70 °C for 12 h.

[0059] Synthesis of ZIF-8@SiOx: Dissolve 0.3 g of the above-prepared ZIF-8 in a mixed solution of 120 mL of ethanol and 198 mL of water, add 1.5 g of CTAB and 1.5 g of 2-MI, ultrasonicate this solution for 0.5 h, then stir for 10 min, and then dropwise add 0.5 mL of TEOS. Next, add 0.5 mL of APTMS, 0.5 mL of TEOS, and 0.5 mL of APTMS every half hour in turn. Then stir the above solution for 2 h, centrifuge it, and wash it several times with deionized water and ethanol, and dry it at 70 °C for 12 h to obtain a core-shell structured ZIF-8@SiOx material.

[0060] Take 0.4 g of the obtained ZIF-8@SiOx and ultrasonically disperse it in 5 ml of DMF. Then mix it with 0.6 g of PAN overnight under stirring to obtain a precursor solution for electrospinning. Subsequently, electrospin the precursor solution to form ZIF-8@SiOx@PAN nanofibers on a release paper. Among them, a 23G stainless steel needle is used as the spinning needle, and the electrospinning parameters are positive voltage: 9.19 KV, negative voltage: -2.49 KV, pushing speed: 0.05 mm / min, stroke set at 200 mm, translation speed: 350 mm / min, and a flat-type receiver is adopted. Stabilize the obtained ZIF-8@SiOx@PAN nanofiber membrane in air at 250 °C for 2 h with a slope of 2 °C·min -1 Then immediately heat-treat it in argon at a heating rate of 5 °C·min -1 for 3 h at 700 °C to obtain Zn-NC@SiOx 0.4 / CNFs electrospun silicon-carbon anode material.

[0061] Finally, cool the calcined fiber membrane to room temperature and press it into a disc with a diameter of 12 mm, which is directly used as an electrode. Assemble a test battery in the same method as in Example 1 for charge-discharge and cycling tests.

[0062] Comparative Example 1:

[0063] Synthesis of ZIF-8 nanoblocks: Dissolve 0.58 g of Zn(NO3)2·6H2O in 20 mL of deionized water and name it Solution A; dissolve 9.08 g of 2-MI and 0.008 g of CTAB in 140 mL of deionized water and name it Solution B. After stirring Solutions A and B for 10 min, add Solution A to Solution B, continue stirring for 5 min, and then let it stand for 12 h. Centrifuge the precipitate at 10000 rpm for 7 min, wash it several times with water and ethanol respectively, and dry the product at 70 °C for 12 h.

[0064] Take 0.2 g of the obtained ZIF-8 and ultrasonically disperse it in 5 ml of DMF. Then mix it with 0.6 g of PAN overnight under stirring to obtain a precursor solution for electrospinning. Subsequently, electrospin the precursor solution to form ZIF-8@PAN nanofibers on a release paper. Among them, a 23G stainless steel needle is used as the spinning needle, and the electrospinning parameters are positive voltage: 9.19 KV, negative voltage: -2.49 KV, pushing speed: 0.05 mm / min, stroke set at 200 mm, translation speed: 350 mm / min, and a flat-type receiver is adopted. Stabilize the ZIF-8@PAN nanofiber membrane in air at 250 °C for 2 h with a slope of 2 °C·min -1 Then immediately heat-treat it in argon at a heating rate of 5 °C·min -1 for 3 h at 700 °C to obtain Zn-NC / CNFs.

[0065] Finally, the calcined fiber membrane was cooled to room temperature and pressed into a disc with a diameter of 12 mm, which was directly used as the electrode. The test battery was assembled and charged / discharged and cycled in the same manner as in Example 1.

[0066] The above are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art within the technical scope disclosed by the present invention can easily think of changes or substitutions, which should be covered within the protection scope of the present invention. Therefore, the protection scope of the present invention should be subject to the protection scope of the claims.

Claims

1. A method for preparing a silicon-carbon negative electrode material based on electrospinning, comprising the following steps: S1. Dissolve zinc nitrate hexahydrate in deionized water, which is named solution A; dissolve 2-methylimidazole and hexadecyltrimethylammonium bromide in deionized water, which is named solution B; S2. After stirring solutions A and B evenly at room temperature, add solution A to solution B, continue stirring for a period of time, then let stand, centrifuge the precipitate, wash it three times with water and anhydrous ethanol respectively, and dry it at 70°C for 12h to obtain ZIF-8 material; S3, dispersing the ZIF-8 material prepared in step S2 in a mixed solution of anhydrous ethanol and water, adding 2-methylimidazole (2-MI) and hexadecyltrimethylammonium bromide (CTAB), uniformly dispersing the solution by ultrasonication, adding two types of organosilicon sources tetraethyl orthosilicate (TEOS) and 3-aminopropyltrimethoxysilane (APTMS) dropwise under stirring, and alternately adding the two organosilicon sources every half an hour, performing the operation 4 times, stirring the above solution, centrifuging, washing with deionized water, and drying; S4, ultrasonically dispersing the material obtained in step S3 in DMF, adding polyacrylonitrile and mixing evenly to obtain a precursor solution, and preparing a fiber membrane using an electrospinning machine; S5. Pre-oxidize the fiber membrane in a muffle furnace at a certain temperature for a period of time, and then heat-treat it under argon protection to obtain a silicon negative electrode material.

2. The preparation method according to claim 1, characterized in that: In the step S1, 0.58 g of zinc nitrate hexahydrate is added and dissolved in 20 ml of deionized water, and 9.08 g of 2-methylimidazole and 0.008 g of hexadecyltrimethylammonium bromide are respectively dissolved in 140 ml of deionized water.

3. The preparation method according to claim 1, characterized in that: The stirring time in step S2 is 5-10 min, and the standing time is 12 h to 36 h.

4. The preparation method according to claim 1, characterized in that: In step S3, 0.3 g of the material ZIF-8 prepared in step S2 was dissolved in a mixed solution of 120 mL of ethanol and 198 mL of water, and 1.5 g of CTAB and 1.5 g of 2-MI were added; the ultrasonic time was 0.5 h, and then stirred for 10 min, and the amount of two types of organic silicon sources tetraethyl orthosilicate (TEOS) and 3-aminopropyltrimethoxysilane (APTMS) added dropwise was 0.5 ml each time; Preferably, in step S3, the usage ratio of two types of organosilicon sources tetraethyl orthosilicate (TEOS) and 3-aminopropyltrimethoxysilane (APTMS) is 1:1 (volume ratio) to 1:1.5 (volume ratio).

5. The preparation method according to claim 1, characterized in that: In step S4, based on 5 ml of DMF, the amount of the material obtained in step S3 is 0.1 g to 0.4 g; Preferably, in step S4, based on 5 ml of DMF, the amount of polyacrylonitrile used is 0.6 g; Preferably, in step S4, the spinning speed of the electrospinning is 0.08 mm / min to 0.12 mm / min, the voltage is 10 KV to 18 KV, and the receiving distance is 12 mm to 15 mm.

6. The preparation method according to claim 1, characterized in that: In step S5, the pre-oxidation temperature is 200-250°C, the stabilization time is 2h, and the heating rate is 2°C·min -1 The calcination temperature in argon was 700 °C, the heat treatment time was 3 h, and the heating rate was 5 °C min -1 .

7. An electrospun silicon-carbon negative electrode material prepared according to the preparation method according to any one of claims 1 to 6.

8. Use of the electrospun silicon-carbon negative electrode material according to claim 7 as a negative electrode material for a lithium-ion battery.

9. A lithium-ion battery, wherein the lithium-ion battery uses the electrospun silicon-carbon negative electrode material according to claim 7 as a negative electrode material.